Activity of Bombus colonies in a submontain environment of Molise region (Bollettino di zoologia agraria e bachicoltura, 2024)
This article shows the results of the observations about Bombus Latr. and PsithyrusLep. species led from 1997 to 2000 in a tipica! submontain environment of Moliseregion. Thirteen species have been found, six of which are new records for theregion. Concerning B. terrestris, lapidarius, pascuorum, pratorum and humilis,the most abundant and constant species, it has been possible to describe the profilesof the colonies cycles. The observations on the flora visited by the bumble beeshave allowed to compile a list of plants with their degree of actractivity and theirimportance as regards to the different species of bumble bees.
Keywords: Bombus; Psithyrus; phenology; Molise; Italy